An Immersed Boundary Method Based on Volume Fraction. (2015) - He, Yuelong; Li, Dun; Liu, Shuai; Ma, Handong
Abstract: The immersed boundary method(IBM) was rapid developed in recent years, because of the ability for the complex configurations and moving bodies simulations. Most of the research on the IBM were focused on the low Mach numberflow, few researchers applied this method to the high Mach number flow problems. A new IB method developed in current paper, which applied the volume fraction to get the cut cell average variables. The values of the variables in the cells that located in the body was determined by the ghost cell method, and the value located in the flow field were gained by power law interpolation. The cases that transonic flow round airfoil and Ma 1.3 shock wave cross wedge were simulated, which showed that the new method could captured the shock wave, expansion wave, shock-vortex interaction, shock reflection, and this method is suitable for the high-speed flow problems.